2009
DOI: 10.1016/j.jmb.2008.10.083
|View full text |Cite
|
Sign up to set email alerts
|

Defining the DNA Substrate Binding Sites on HIV-1 Integrase

Abstract: A tetramer model for HIV-1 IN with DNA representing the LTR termini was previously assembled to predict the IN residues that interact with the LTR termini; these predictions were experimentally verified for nine amino acid residues (Chen et al, J. Biol. Chem. 281, 4173-4182 (2006)). In a similar strategy the unique amino acids found in ASV IN rather than HIV-1 or MPMV IN were substituted into the structurally related positions of HIV-1 IN. Substitutions of six additional residues (Q44, L68, E69, D229, S230 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…However, we suggest that Q148/N155 residues interact with the sterically and energetically more favorable terminal unpaired adenine, consistent with previous data showing post-3 0 -processing contact between Q148 and the 5 0 -AC overhang (Chiu and Davies, 2004;Esposito and Craigie, 1998) and the theoretical model of the IN-DNA complex (Dolan et al, 2009). By contrast, the Q148R mutant preferentially established specific interactions by binding the two bases of a pair, either A-T or G-C, simultaneously.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we suggest that Q148/N155 residues interact with the sterically and energetically more favorable terminal unpaired adenine, consistent with previous data showing post-3 0 -processing contact between Q148 and the 5 0 -AC overhang (Chiu and Davies, 2004;Esposito and Craigie, 1998) and the theoretical model of the IN-DNA complex (Dolan et al, 2009). By contrast, the Q148R mutant preferentially established specific interactions by binding the two bases of a pair, either A-T or G-C, simultaneously.…”
Section: Discussionsupporting
confidence: 91%
“…This result supports the validity of our model. A recent theoretical prediction for DNA substrate binding sites on HIV-1 IN indicated that amino acids 139-152 constitute a binding site that includes Q148, together with Q137, Q146, and N144 Dolan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…already been shown to be important for DNA binding and 3= processing (15,38), has more DNA interactions than are obvious from modeling. A more dramatic spatial and orientation shift of R262 relative to its wild-type position was observed in the inner integrase subunits (Fig.…”
Section: Isolation Of R263k Mutant Viruses With Dtgmentioning
confidence: 99%
“…Elegant knockdown studies have demonstrated the importance of LEDGF/p75 in integration targeting and integrase stability (27,48,50,62,77). Additional studies have explored the link between chromosomal DNA structure and integration, suggesting that nucleosome-bound DNA may be more susceptible to integration due to conformational changes (16,25,63,64,79).…”
Section: Quiescent Cd4mentioning
confidence: 99%